BENEFICIATION OF SILVINITE ORES BY HALURGICAL METHOD (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
The halurgical method, also known as the thermal-solution treatment, represents an alternative route for potash extraction from silvinite ores, especially in deposits where flotation efficiency is limited due to fine intergrowths or high halite content. This approach involves dissolving potassium chloride selectively from crushed ore by manipulating temperature, solution concentration, and crystallization conditions. The present thesis examines the principles, process flow, and technological parameters of silvinite beneficiation through halurgical processing. The study outlines key stages including ore dissolution in saturated brine, selective crystallization of KCl, and recovery of high-purity potassium salts. Special attention is paid to thermodynamic modeling, energy requirements, and brine recycling. The halurgical method is evaluated in terms of its industrial applicability, energy efficiency, and environmental impact. The findings show that with appropriate control over temperature and brine composition, the halurgical method can achieve over 90% KCl recovery, offering a viable complement to flotation-based techniques in specific geological settings.